Epithelial Na+ Channel: Reciprocal Control by COMMD10 and Nedd4-2 - Ware, Adam W.; Cheung, Tanya T.; Rasulov, Sahib; Burstein, Ezra; McDonald, Fiona J. (Frontiers in Physiology, 2018)
Optimal function of the epithelial sodium channel (ENaC) in the distal nephron is key to the kidney’s long-term control of salt homeostasis and blood pressure. Multiple pathways alter ENaC cell surface populations, including correct processing and trafficking in the secretory pathway to the cell surface, and retrieval from the cell surface through ubiquitination by the ubiquitin ligase Nedd4-2, clathrin-mediated endocytosis, and sorting in the endosomal system. Members of the Copper Metabolism Murr1 Domain containing (COMMD) family of ten proteins are known to interact with ENaC. COMMD1, 3 and 9 have been shown to down-regulate ENaC, most likely through Nedd4-2, however the other COMMD family members remain uncharacterized. To investigate the effects of the uncharacterized COMMD10 protein on ENaC trafficking and function, the interaction of ENaC and COMMD10 was confirmed. Stable COMMD10 knockdown decreased ENaC current and this decreased current was associated with increased Nedd4-2 protein, a known negative regulator of ENaC. However, inhibition of Nedd4-2’s ubiquitination of ENaC was only able to partially rescue the observed reduction in current. Stable COMMD10 knockdown results in defects both in endocytosis and recycling of transferrin suggesting COMMD10 likely interacts with multiple pathways to regulate ENaC and therefore could be involved in the long-term control of blood pressure.